Dark Law: Perspective Of Space And Time - Agus Pandoman (Asas Wa Tandhim: Jurnal Hukum, Pendidikan Dan Sosial Keagamaan, 2026)
This article examines the concept of "dark law" — the manipulative actualization of law that operates in opaque spaces and times — and its implications for certainty, justice, and order. Law comprises three essential elements: certainty (nature), justice (function), and order (purpose). When legal manifestations (statutes, regulations, and practices) lose one or more of these elements, they become "dark law." Using normative legal research and theoretical reflection, this paper describes how dark spaces and periods facilitate legal manipulation, enabling illicit transactions and undermining public trust. The article argues for institutional transparency and civic oversight to prevent the rise and entrenchment of dark law.